"I can almost taste it:" Why people with strong positive emotions experience higher levels of food craving, salivation and eating intentions. Issue 1 (15th July 2014) - Moore, David J.; Konrath, Sara
Abstract: The goal of this paper is to examine whether individual differences in affect intensity predict people's responses to food advertisements. In doing so, we aim to uncover individual differences and situational factors that are associated with higher food cravings and other consumption‐related responses. Studies 1 and 2 identified three mediators (emotional memories, weak impulse control, and the intensity of pleasure anticipation) which indirectly link affect intensity to food cravings and behavioral intentions. Studies 3 and 4 identified two moderators (vividness of advertisement, dieting status of participants) of the relationship between affect intensity and consumption‐related outcomes. In Study 3 high affect intensity individuals reported stronger food cravings only in response to vivid advertising appeals. In Study 4, respondents with high levels of positive affectivity, a sub‐dimension of affect intensity, experienced increased salivation, but especially when they were dieters exposed to vivid food images. Implications for theory development and for marketing and public policy strategists are discussed.